Cu–Catalyzed Tandem Oxidation of N‐Substituted Indolines to Isatins. Issue 46 (10th December 2018) - Gao, Shanshan; Zheng, Junliang; Ge, Guoping; Luo, Junfei
Abstract: The direct transformation of N ‐substituted indoline to isatin derivatives has been developed, this reaction employed cheap Cu catalyst and aqueous tert ‐butyl hydroperoxide as an oxidant. Primary mechanism studies suggested that the indolines was initially oxidized to indoles which further undergo Cu‐catalyzed oxidation to isatins. Abstract : The N ‐substituted indolines have been found to undergo a tandem oxidation process, delivering into the corresponding isatin derivatives within a single synthetic operation.